DAMPAK KEBERADAAN MINIMARKET TERHADAP PENJUALAN TOKO KELONTONG DI KECAMATAN TELUKDALAM STUDI KASUS: INDOMARET DAN ALFAMIDI - Panjaitan, Viki Albert Kusuma (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
The purpose of this research is (1) To find out the sales of grocery stores before and after the presence of the Indomaret and Alfamidi minimarket, (2) To know the impact of the Presence of Indomaret and Alfamidi minarket. This is a field research with a qualitative descriptive approach, in which the researchers conducted interviews with retailers of 25 (twenty-five) people. The difficulty of competition experienced by grocery stores has led to a decrease in the number of consumers who buy, leading to a decline in sales. It is advisable for merchants of grocery stores to make efforts to maintain their business such as improving service, being friendly and more complementary to the products to be sold. For the local government it is better to pay more attention to the local entrepreneurs and pay attention to every permission to build a mini-market so as not to harm the local enterprises.